(untitled) (Proceedings of the International Conference on Public Health, 2017)
The population of adolescents in Indonesia is almost 30% of the total population of Indonesia. This figure is quite large as a potential asset for the country. Today the percentage of adolescents who engage in high-risk behavior is quite high. Data of Health Ministry that show the number of HIV cases in productive age is increasing from year to year. Therefore, youth health programs are a national priority. Many teenage health programs have been conducted from various sectors. This study aims to identify adolescent perceptions on the implementation of youth health programs. Teenagers, in this case, are grouped into 2, namely as a peer educator and as the target program (user). This study looked at adolescent perceptions in relation to the strategic steps of adolescent health programs. This research is descriptive research by using a qualitative method, subjects of research is adolescent stakeholder which is consisting of school’s teenagers, adolescent community, mosque teenagers and street teenagers. Data were collected through interviews with 10 peer educators (schools and communities), interviews of 2 teenage street users, 3 teenage mosque interviews, 24 FGD participants (2 FGDs in School and 2 FGDs in the community). The results showed that the adolescent group of providers and users are still categorized as ’observers’ (support, weak power, and passive involvement) in the implementation of the strategic steps of youth health programs. There are even teenagers from community youth groups who have not been exposed to teenage health programs. Adolescent health programs should involve teenagers from planning until evaluation. Therefore, the existing program suits needs and abilities of adolescents (from by for teenagers).